2018
DOI: 10.12669/pjms.346.15833
|View full text |Cite
|
Sign up to set email alerts
|

Radiological and clinical outcomes in patients undergoing anterior cervical discectomy and fusion: Comparing titanium and PEEK (polyetheretherketone) cages

Abstract: Objectives:To study clinical and radiological outcomes in patients who had undergone the procedure of anterior cervical discectomy and fusion with titanium or PEEK (polyetheretherketone) cages for cervical disc prolapse.Methods:This is a retrospective/non-randomized study which was conducted at the Combined Military Hospital Peshawar. Study interval was four years from 1st October, 2010 to 31st September, 2014. Total number of included patients were 149. All of the patients had undergone the procedure of anter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Furthermore, it provides long-term stability as Ti cages supported bone growth into and around the implant margins, with the porous structure allowing for host bone ingrowth and bone bridging through the device, hence explaining the superior fusion rates as compared to PEEK cages [22]. Most studies included in this metaanalysis showed that fusion rates of Ti cages were superior or at least similar to PEEK cages [4,5,10,11,17,[23][24][25][26], with the exception of Chou et al and Niu et al [27,28], who had found that PEEK cages achieved better fusion. In the studies by Chou and Niu et al, the PEEK cages utilized incorporated 2 titanium spikes on the upper and lower frames, which the authors hypothesize offer a fixation mechanism, hence contributing to better stability leading to fusion.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Furthermore, it provides long-term stability as Ti cages supported bone growth into and around the implant margins, with the porous structure allowing for host bone ingrowth and bone bridging through the device, hence explaining the superior fusion rates as compared to PEEK cages [22]. Most studies included in this metaanalysis showed that fusion rates of Ti cages were superior or at least similar to PEEK cages [4,5,10,11,17,[23][24][25][26], with the exception of Chou et al and Niu et al [27,28], who had found that PEEK cages achieved better fusion. In the studies by Chou and Niu et al, the PEEK cages utilized incorporated 2 titanium spikes on the upper and lower frames, which the authors hypothesize offer a fixation mechanism, hence contributing to better stability leading to fusion.…”
Section: Discussionmentioning
confidence: 89%
“…While PEEK cages were noted to have a trend towards a lower rate of subsidence in our meta-analysis, there was substantial heterogeneity amongst the 8 studies, with 2 studies showing Ti cages causing increased subsidence [5,28], 4 studies showing with no difference between both groups [4,17,26,27], and 2 studies showing no subsidence even at the final follow-up [10,24]. In patients with spondylodiscitis, Schomacher et al reported a high rate of subsidence in both groups (67% PEEK group, 75% of Ti group) [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers have proposed that, combining pixel information of different scales can extract the best size information; some researchers believe that, reducing the size of the convolution kernel can improve the running speed of the neural network. [7][8][9][10] The CT image reconstruction algorithm can effectively remove image noise and improve image quality, assisting physicians in diagnosing diseases. With the rapid development of deep learning, many deep learning networks are used to process CT images.…”
Section: Resultsmentioning
confidence: 99%